Diagnostic value of measuring the amount of 6-hydroxymelatonin sulfate in urine in postmenopausal women with functional abdominal pain - Wiśniewska-Jarosińska, Maria; Chojnacki, Jan; Pawłowicz, Monika; Klupińska, Grażyna; Chojnacki, Cezary (Menopause Review/Przegląd Menopauzalny, 2009)
Melatonin secretion decreases with age. It has been suggested that this process especially occurs faster in postmenopausal women. However, it is not explained whether this decrease depends on the reduced function of the pineal gland or rather on the enterochromaffin cells of the alimentary tract. Similarly, it remains unknown whether the gastrointestinal aliments in the postmenopausal period could be associated with the decreased melatonin secretion. Aim of the study: The study aimed at evaluating 24-hour urinary excretion of the main melatonin metabolite – 6-hydroxymelatonin sulfate (6-HMS) – in correlation with the occurrence and the severity of functional abdominal pain in postmenopausal women. Material and methods: The study comprised 77 women. There were three study groups distinguished: Group I – 25 clinically healthy women, aged 33–40 years (K); group II – 25 postmenopausal women, aged 55–65 years, without complaints from the gastrointestinal tract; group III – 32 women, aged 55–64 years, with persistent functional abdominal pain (class D according to the Rome III Criteria). The women with other diseases, among them with clinically evident depression or on hormonal substitutive therapy, were excluded from the study. The amount of 6-HMS sulfate excreted in 24-hour urine collection was measured by ELISA method applying IBL antibodies (the catalogue number RE54031). Results: The amounts of urinary 6-HMS excreted in 24 hours were as follows: group I – 19.96 ±7.02 µg/24 h, group II – 16.96 ±6.79 µg/24 h (p < 0.05), group III – 12.48 ±4.32 µg/24 h (p < 0.01). The lowest value of the urinary 6-HMS was noted in women with the severe abdominal pain (9.60 ±1.69 µg/24 h) and in those with sleep disturbances (10.01 ±1.60 µg/24 h) deteriorating their quality of life. Conclusions: 1. In postmenopausal women with functional abdominal pain melatonin secretion is decreased. 2. Evaluation of the amount of urinary 6-HMS excreted in 24 hours may be considered a useful marker in deciding about the combined therapy of the above mentioned disorders.